EXPLORING THE READING COMMAND FROM QUR’ANIC STUDIES AND ITS BENEFITS - Mastur Thoyib (Jurnal Intelek Dan Cendikiawan Nusantara, 2024)
The command to read, which stems from a heavenly revelation in Hira's cave, establishes literacy as a sacred and transforming act for mankind. The Quranic phrase expressly advises the Prophet Muhammad to recite, underlining the intrinsic connection between reading and knowledge. This divine directive is strengthened by the Prophet's hadiths, which emphasize the importance of each letter of the Quran. The complex beauty of the Arabic language, as well as the numerical focus on multiplying rewards for each letter, highlight the Quran's precise perfection. The revelation of specific verses in reaction to historical events, as explained by Asbab Nuzul, gives contextual richness to divine instruction, supporting the Quran's applicability across time. Using literature review, this research enhances some results that the advice and virtue of reading the Quran should serve as a constant source of encouragement for Muslims to enhance their understanding, encouraging an active and enriching engagement with the sacred text throughout their lives. There are numerous ways to become accustomed to reading, but not everyone is encouraged to read as a leisurely activity. Most folks only read what's important. However, it is a loss if you are unaware of the benefits and significant influence that reading for enjoyment provides. Reading has a high correlation with human imagination, excitement, and creativity, making it less appealing. We must treat pleasure reading with the same seriousness as academic reading, because reading will be more enjoyable once it becomes a habit.